Illicit drugs and the decline of the middle class - Volker Grossmann; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
Empirical evidence for the U.S. suggests that the consumption of intoxicants increases in association with the socio-economic deprivation of the middle-class. To explore the underlying mechanisms, we set up a task-based labor market model with endogenous mental health status and a health care system. The decline of tasks that were historically performed by the middle class and the associated decline in relative wages and socio-economic status increases the share of mentally ill middle class workers. Mentally ill workers can mitigate their hardships by the intake of illicit drugs or by consuming health goods. We argue that explaining the drug epidemic of the U.S. middle class requires an interaction of socio-economic decline and falling opioid prices. One factor in isolation is typically insufficient. Our analysis also points to a central role of the health care system. In our model, extending mental health care could motivate the mentally ill to abstain from illicit drug consumption.
Keywords: I10; H51; 330; Socio-economic deprivation; Intoxicants; Health insurance; Mental health; Middle class